Contribuições ao status taxonômico de Ancistrus Kner, 1854 (Loricariidae, Ancistrini) da bacia do Rio Paraná, Brasil baseados em marcadores citogenéticos e moleculares - Prizon, Ana Camila (2018)
Ancistrus Kner, 1854 is one of the most specious groups of the Ancistrini tribe comprising 69 described species. Currently, karyotypes are known for 33 Ancistrus species, although most of these have not yet been formally identified. The karyotype data available for this genus indicate considerable chromosome diversity, with diploid numbers varying from 2n = 34 to 2n = 54. In addition to numerical diversity, chromosome structure variation has been reported, including karyotypes with sex chromosomes, distinct heterochromatin distribution patterns and repetitive DNA sequences, with differences in the number and location of ribosomal DNA sites, especially the 5S rDNA sites. The karyotypic descriptions cover mainly the species from the basins of Paraguay, in the states of Mato Grosso and the Amazon. From the taxonomic point of view, only one species of Ancistrus was recorded in the upper Paraná River basin, identified as Ancistrus cirrhosus by Valenciennes 1836, collected in the region of Missiones, Argentina. However, the wide variation found in the morphology and color of the populations sampled in the tributaries of the Paraná River (PR), became difficult to establish the taxonomic status of the Ancistrus specimens, suggesting that Ancistrus cirrhosus is not the only species found in this basin. The inclusion of genetic data in taxonomy and evolution studies had a profound influence on the understanding of species diversity for the neotropical region and the application of integrative taxonomic methods, combining different lines of evidence (DNA sequences, chromosome data and morphological characteristics) altered our perception of the region's biological diversity and contributed to the increased rate of discovery of new species, especially in cryptic lineages. In this context, species delimitation tests using DNA sequences can be highly informative, allowing more systematic documentation of species diversity. Besides that, due to the extensive karyotype variation found for the genus Ancistrus, it is possible that some repetitive elements may be responsible for much of the karyotype variation of these species, since their involvement in karyotype diversification has already been reported. Among the several repetitive DNA sequences that are present in the eukaryotic genome, the transposable elements (TEs) are the most representative. They are able to move within the genome, inserting themselves into new sites, close, or even within gene sequences. The tandem-organized repetitive DNA sequences are arranged in a sequential array of repeating units, ranging from 150?180 bps to 300?360 bps and microsatellites (or short tandem repeats) are made up of short sequences of one to six nucleotides. Thus, given the assumption that there is cryptic diversity in the Ancistrus populations of the rivers and streams of the Upper Paraná basin, in this study we combine chromosome and DNA sequence data to evaluate the taxonomic status of these populations. At the same time, in order to formulate hypotheses about the mechanisms that led to karyotypic diversification among them, we also included the physical mapping of repetitive tandem sequences (telomeric and microsatellite repeats) and dispersed in the genome (Rex-3 retrotransposable element), for a better understanding of the organization of the Ancistrus genome of this basin. In our combined analysis, we recovered five distinct lineages among the analyzed populations, clearly observed in our molecular analyzes (phylogenetic inferences and by the species delimitation method - GYMC). Although all lineages presented distinct chromosomal formulas, all the specimens presented 2n = 50 chromosomes. Thus, the data suggested at least four candidate species of Ancistrus which may be present in the Paraná basin, in addition to A. cirrhosus. Among the karyotypes found for each lineage, we highlight the populations of 19 Stream and Keller River, which presented 12m+18sm+12st+8a (females) and 11m+18sm+13st+8a (males), consistent with a XX/XY sexual system. The X (metacentric) chromosome of the populations varied in amount and distribution of heterochromatin blocks and could not be distinguished from the Y chromosome (subtelocentric) by the C-band. Clusters of 18S rDNA were observed on a single pair of chromosomes in seven analyzed Ancistrus populations, but in different positions, in some cases, in synteny with the 5S rDNA sites. Multiple sites of 5S were observed in all populations. The physical mapping using as probe the Rex-3 element isolated from a specimen of Ancistrus sp. of the Keller River revealed fluorescent signals scattered across the chromosomes of all seven Ancistrus populations analyzed, with some signals associated with heterochromatic blocks and rDNA sites. The presence of this element distributed throughout the genome could explain the presence of the multiple sites of 5S rDNA, as well as the synteny break between the sites of rDNA 18 and 5S detected in some populations, being the basal condition for the genus Ancistrus. The nucleotide sequences of Rex-3 element revealed high similarity to sequences from the same element deposited in the online BLAST/CENSOR database. Alignment of the presumed amino acid sequence with X. maculatus revealed highly conserved reverse transcriptase domains, suggesting that this element is potentially active in this genome and may have contributed to the dissemination of the copies detected by FISH. Fluorescent in situ hybridization (FISH) of the microsatellites (CA)15 and (GA)15 provided preferential band pattern in the subterminal and interstitial regions of most chromosome arms, with some signs appearing stronger and more extended than others. Hybridization signals were observed in the repetitive sequences accumulated in the heteromorphic sexual pair (XY) of Ancistrus sp. of the Keller River and 19 Stream, revealing a possible involvement of these repetitive sequences (Rex-3 and CA/GA) in the differentiation of heteromorphic sex chromosomes. The karyotypic diversity detected in Ancistrus may be a consequence of the presence of repetitive elements (Rex-3 and GA/CA microsatellites), which were scattered throughout the chromosomal complement, indicating that these two classes of repetitive DNA sequences have played an important role in the differentiation of the genome of this taxon. Thus, the inferences obtained in the present study from a combined approach of molecular and cytogenetics analyzes was especially important due to the lack of diagnostic features in the morphology of these fishes, which allowed us to differentiate five distinct lineages of Ancistrus, reinforcing the hypothesis of the presence of at least four candidate species in the upper Paraná basin, besides of the Ancistrus cirrhosus, previously described